The Role of a Notary in Making a Choice of Law of an International Business Contract - Merry Koesnadi; John Pieris; Aarce Tehupeiory (International Journal of Social Service and Research, 2023)
As a consequence of the globalization era, legal relations between the world community are open and very easy. The International Business Contract is one of the legal relations used to facilitate cooperation between them, but sometimes the ease in cooperation often faces obstacles in the event of a dispute between them, for example wrong one party does not fulfill its promises (achievements). It is quite common that the parties involved in a certain business are faced with disputes resulting from the legal contract they previously made. To anticipate such happenings, they always include choices in the contract clause although they sometimes skip to do so. The lack of such a clause will bring about a problem which is law should they refer to to solve the dispute. This is where the role of a notary is very important in making a choice of law for international business contract. The role of notary is closely related to his authority, namely making authentic deeds. The Method used in normative juridicial research which is carried out as an effort to obtain the necessary data related to the problem. The data source is secondary as consisting of primary legal materials, secondary legal materials, and tertiary legal materials. In addition, primary data is also used to support secondary data legal out using qualitative juridicial analysis methods. From the research results it can be obtained that the choice of law must be determined based on theory and principles in international private law. The role of a notary in making a choice of law for international business contract is limited to providing suggestions or legal counseling on the choice of law. Notary may not determine the choice of law in the international business contracts they make. But only given reccomendations to their clients.